Description Of Compliance With Bontobahari Mother Consuming Vitamin A In Bontobahari Puskesmas - Iramayasari; Irmawati (Jurnal Life Birth, 2020)
Based on data from the World Health Organization ((WHO), it is stated that mothers and babies who are breastfed will benefit from giving one high-dose Vitamin A capsule (200,000 IU). Various studies have shown that giving high doses of Vitamin A capsules (200,000 IU) previously recommended it was deemed inadequate. Vitamin A is one of the vitamins needed and is useful for the growth of cells, teeth, bones, development of vision, and increasing body resistance to infection. The aim of the research was to know the description of the compliance of postpartum mothers in consuming vitamin A at the Bontobahari Community Health Center in 2018. This research was conducted using a descriptive survey research method, which is a research method with the aim of knowing the description or description of health problems in the form of risk factors and effects. The technique used in this research is the Accidental Sampling technique. The population and sample in this study were part of the postpartum mothers in the Bontobahari puskesmas area, totaling 3 people. From the research that has been done, it is found that out of 33 respondents, 24 people (72.7%) obedient to consuming Vitamin A, and 9 people (27.3%) who are not obedient to consuming Vitamin A. The conclusion of this research. Suggestions from the results of this study are that the results of this research can be used as information and input to postpartum mothers regarding adherence to consuming Vitamin A.